Exon skipping creates novel splice variants of DMC1 gene in ruminants. Issue 2 (April 2016) - Ahlawat, S.; Chopra, M.; Jaiswal, L.; Sharma, R.; Arora, R.; Brahma, B.; Lal, S.V.; De, S.
Abstract: Disrupted meiotic cDNA1 (DMC1) recombinase plays a pivotal role in homology search and strand exchange reactions during meiotic homologous recombination. In the present study, full length coding sequence of DMC1 gene was sequence characterized for the first time from four ruminant species (cattle, buffalo, sheep and goat) and phylogenetic relationship of ruminant DMC1 with other eukaryotes was analyzed. DMC1 gene encodes a putative protein of 340 amino acids in cattle, sheep and buffalo and 341 amino acids in goat. A high degree of evolutionary conservation at both nucleotide and amino acid level was observed for the four ruminant orthologs. In cattle and sheep, novel alternatively spliced mRNAs with skipping of exons 7 and 8 (Transcript variant 1, TV1) were isolated in addition to the full length (FL) transcript. Novel transcript variants with partial skipping of exon 7 and complete skipping of exon 8 (Transcript variant 2, TV2) were found in sheep and goat. The presence of these variants was validated by amplifying cDNA isolated from testis tissue of ruminants using two oligonucleotides flanking the deleted region. To accurately estimate their relative proportions, real-time PCR was performed using primers specific for each variant. Expression level of DMC1-FL was significantly higher than that of TV1 in cattle and TV2 in goat (P < 0.05). Relative ratio for expression of DMC1-FL: TV1: TV2 in sheep was 6.78: 1.43: 1. In-silico analysis revealed presence of splice variants of DMC1 gene across other mammalian species underpinning the role of alternative splicing in functional innovation. Highlights: DMC1 recombinase was sequence characterized for the first time in four ruminant species. Novel alternatively spliced mRNAs with skipping of exons 7 and 8 were also isolated. Presence of variants was validated by amplifying cDNA using primers flanking the deleted region. Real-time PCR was performed to estimate relative proportion of each variant. Alternative splicing was observed to be an evolutionarily conserved process across species.